Embedded active impedance source inverter: Analysis and implementation. (29th September 2022) - Ranjbarizad, Vida; Babaei, Ebrahim; Cecati, Carlo
Abstract: In this paper, a new active impedance source inverter with a suitable control method based on the pulse‐width modulation (PWM) technique is proposed. Based on the proposed control method, the analysis of the proposed inverter in different operating modes is given, and its boost factor is calculated. Then, the fundamental equations to design the values of inductors and capacitors are presented. Also, comparative analysis from different points of view, such as boost factor, voltage stresses on capacitors, and total voltage blocked by diodes and switches, between the proposed topology and conventional structures to examine the advantage and disadvantages is done. Comparison results show that the proposed topology has fewer voltage stresses on capacitors and total voltage blocked by diodes and switches. Also, it has fewer elements and continues input current and a more straightforward structure. The proposed topology's losses and efficiency at different loads are fully calculated. Finally, a prototype of the proposed topology is designed, and its experimental results along with simulation results by PSCAD to check the proposed topology's good performance and correctness of the obtained equations in different operating modes are provided. Abstract : In this paper, a new active impedance source inverter with a suitable control method based on the pulse width modulation (PWM) technique is proposed. Based on the proposed control method, the analysis of the proposed inverter in different operating modes is given, and its boost factor is calculated. Then, the fundamental equations to design the values of inductors and capacitors are presented.